Frey syndrome - Egierska, Dominika Magdalena; Perszke, Michał; Grzelewski, Aleksy; Cieślak, Kamil; Berliński, Miłosz; Świenc, Witold; Tokarczuk, Oskar (Journal of Education, Health and Sport, 2022)
Frey syndrome is a condition of gustatory sweating and hyperemia related to damage of the auriculotemporal nerve. It affects around 80% of patients after parotidectomy. Syndrome may be easily diagnosed with an iodine-starch test, even in patients without symptoms, which are about 20% depending on studies. Authors searched PubMed and Google Scholar using searchterms Frey syndrome, auriculotemporal nerve, greater auricular nerve, tympanic nerve, parotidectomy. We manually searched the references of selected articles for additional relevant articles. We selected articles relevant to a general medicine readership and prioritized systematic reviews, clinical practice guidelines and cases. The literature contains the latest reports on Frey syndrome. Symptoms of Frey syndrome are: redding of the skin due to vasodilatation, excessive sweating or tingling and burning sensation of the cheek skin. Clinicians should pay attention to frey syndrome in patients after parotid gland surgery. Treatment includes botulinum toxin type A most commonly, topical injection of alcohol, scopolamine, glycopyrrolate and less common surgical treatment including transection of auriculotemporal nerve. Frey syndrome is not such a rare disease and should be always considered by clinicians because it may worsen the quality of patients' life.